A New Method For Teaching Classical Arabic Poetry To Non-Native Speakers - Ahmad H.Osman, Rahmah; Mahmud, Murni; Mohd Ghalib, Mohd Feham; Ahmed Mahmoud, Ahmed Ragheb (2017)
The copyright is teaching materials on Classical Arabic Poetry To Non-Native Speakers